Efektifitas Implementasi Kebijakan Kurikulum 2013 pada Satuan Pendidikan di Kota Ambon dan Kabupaten Maluku Tengah - Muhammad Nur Matdoan (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2020)
The purpose of this study was to determine: 1) the effectiveness of 2013 curriculum planning in educationalunits (SD / MI, SMP / MTs, SMA / MA, SMK) in Ambon City and Central Maluku Regency 2) the effectiveness of 2013curriculum development in educational units in Ambon City and Central Maluku Regency 3) the effectiveness of the 2013curriculum implementation in the education units of Ambon City and Central Maluku Regency. This type of research is descriptivequalitative using unstructured interview guidelines for data collection purposes with 42 informants. The research results are; The education unit in carrying out the planning, both the education unit and the education and culture office, has formed a curriculum development team (TPK) in Ambon City whose steps are; (1) for the city level, the team works to provide material in the form of training to school principals, supervisors, teacher working groups (KKG) and subject teacher deliberations (MGMP) and holds workshops for guiding teachers, especially in the context of efforts to increase teacher competence. (2) The parties involved in the curriculum development team consist of; school committees, education boards, education offices, professional associations, school principals, the world of industry and the world of work (DUDI), natural resources and socio-culture, all work together to monitor and evaluate to validate the curriculum documents that have been made.